BENTUK PINTU MASUK SARANG TRIGONA SPP DI KAWASAN HUTAN MANGROVE SURYA PERDANA MANDIRI KELURAHAN SETAPUK BESAR SINGKAWANG UTARA - Febrianti, Febrianti; M, Iskandar A; Muflihati, Muflihati (Universitas Tanjungpura, 2020)
The Trigona spp (kelulut) bee is a non-stinging honey bee that belongs to the Apidae family. Kelulut is a social insect that lives in groups in a colony, where this bee colony defends itself by biting if disturbed. Kelulut usually make nests in tree holes, wall gaps and bamboo holes in the house, with simple materials that are used as nests such as wooden boxes, pieces of bamboo, coconut fruit, coconut shells, and earthen pots as long as the nesting material is tightly closed. Bee hives are a place of refuge for a bee colony from bacteria, fungi, viruses, and predators, as well as a place for honey, bee pollen, and bee eggs to grow. Kelulut nests are built from resin material derived from plants, besides that there is a door to the nest which is decorated with a funnel made of resin and has various shapes, some are short and some are long, depending on the type which serves as a place to enter and exit colony members. The entrance and exit of the nest not only serves as a pathway for entry and exit, but also serves as a marker for the nest. Kelulut nest entrances have various shapes, including funnel, oval, elliptical, round and irregular or without protrusions at the entrance. This study aims to determine the shape of the entrance to the Trigona spp nest in the Surya Perdana Mandiri Mangrove Forest Area. The method used is a survey, with roaming techniques. Observations were made on trees with kelulut nests. Data analysis using descriptive qualitative. The results found 2 species of kelulut, namely Heterotrigona itama Cockerell and Tetragonula laeviceps Smith. H.itama bees have 6 the shape of entrance and T.laeviceps bees have 4 the shape of entrance. H.itama bees have a funnel at the entrance and there are propolis around the nest. The H.itama entrance has a different shape in the form of a long and slender funnel and a short and large funnel. In addition, the funnel has a variety of colors, black, golden yellow, light brown, and dark brown. While T.laeviceps species do not have a funnel or nest entrance. This type only makes a hole as a place to enter and exit the nest and there is no propolis found around the nest.Keywords: Heterotrigona, mangrove, nest entrance, tetragonula, trigona